Meta-analysis of magnetic resonance imaging accuracy for diagnosis of oral cancer. - Marcelo Aldrighi Moreira; Luiza Silveira Lessa; Francieli Regina Bortoli; Abigail Lopes; Eduardo Picolo Xavier; Renan Antonio Ceretta; Fernanda Guglielmi Faustini Sônego; Cristiane Damiani Tomasi; Patricia Duarte Simões Pires; Luciane Bisognin Ceretta; Ingrid Dalira Schweigert Perry; Priscyla Waleska Simões (PLoS ONE)
Objective To establish the diagnostic accuracy of magnetic resonance imaging (MRI) as an auxiliary means for the diagnosis of oral cancer through a systematic review and meta-analysis. Methods An exhaustive search of publications from 1986 to 2016 was performed of Medline, Embase and Cochrane (and related databases), including grey literature. Primary diagnostic accuracy studies that assessed oral cancer (target condition) using MRI (index test) were included. Diagnostic threshold, sensitivity and meta-regression analyses were performed. A meta-analysis was performed using Meta-DiSc® v. 1.4 software. Results A total of 24 primary studies were assessed, comprising 1,403 oral cancer lesions. Nine studies used diffusion-weighted MRI, with a diagnostic odds ratio (DOR) of 30.7 (95% confidence interval [CI]: 12.7-74.3) and area under the curve (AUC) of 0.917 (95% CI: 0.915-0.918); seven studies used dynamic contrast-enhanced MRI, with a DOR of 48.1 (95%CI: 22.4-103.2) and AUC of 0.936 (95% CI: 0.934-0.937); and 13 studies used traditional MRI, with a DOR of 23.9 (95%CI: 13.2-43.3) and AUC of 0.894 (95% CI: 0.894-0.895). Meta-regression analysis indicated that the magnetic field strength may have influenced the heterogeneity of the results obtained (p = 0.0233) using traditional MRI. Sensitivity analysis revealed a discrete reduction of inconsistency in some subgroups. Conclusion The three types of MRI assessed exhibited satisfactory accuracy compared to biopsy. Considering the relevance of early treatment and screening and that better health care results in improved survival rates and quality of life for oral cancer patients, we suggest the use of MRI as a part of the pre-treatment and monitoring protocol at public health services.